Lean six sigma implementation for it service delivery : case study and improvement plan proposal - Peh, Wendy (2021)
The purpose of this paper is to show the root causes, result, challenges and implementation of lean six sigma implementation in Company D, which is one of the IT service companies in Malaysia. Lean Six Sigma implemented in Company D with the purpose of finding the root causes of bad service, high cost, low morale and productivity. DMAIC methodology was used in this study. Fishbone diagram and survey was used to find out the current issue and a list of improvement plans were proposed to the management. Interview was conducted after the implementation to review its effectiveness. The top 3 root causes found through fishbone diagram and FMEA are, management, operation and engineers. The study shows only minor improvements as there was a lack of support and commitment from the management. However, the study proved that Lean Six Sigma implementation in the IT service sector brings positive outcomes even though there were only minor improvements due to the lack of support and commitment from management. Suggestions were provided for further study in order to optimize the successfulness of Lean Six Sigma implementation. (Abstract by author)